La incidencia del control de inventarios en la rentabilidad en la empresa Colrest S.A durante el ejercicio económico 2017. - Sagal Heredia, Verónica Gabriela (2018)
The present research work was carried out to analyze the incidence of inventory control in the company COLRESTA S.A. during the fiscal year 2017, and its impact on corporate profitability. It is for this reason that inventory control is the essence of the company, that is to say, the company´s core due to the impact it can cause inside and outside of it because with proper control it will be possible to reduce risks. The research work was developed in the company COLREST S.A., analyzing the variables of study: The incidence of inventory control and profitability. The methodology used was the deductive and exploratory method, the general knowledge of variables was taken to deduce what happened in the company; the whole data information in documents and financial reports was taken where the events took place, therefore the type of research was documentary and field in the same way it was guided by the COSO I model. Have an adequate internal inventory control will help the company to obtain suitable and useful inventories for increasing profitability based on the benefits obtained during the fiscal year. The results obtained in the research will be achieved through techniques and field work that will allow an analysis about the reality in the company. The information is obtained from the personnel that works in the company where it will be determined if the processes developed in the warehouse area are adequate and correct to control the merchandise, surveys and interviews were applied to COLREST SA personnel, in accordance with its relation to the object of study. The information and its respective analysis let us to draw conclusions and recommendations.